Consumer behavior - Santos, Joao Heitor de Avila (Toronto Academic Press, 2024)
Consumer behavior refers to the actions and decisions made by individuals and households when purchasing goods and services. This book explores how consumers make decisions when purchasing goods or services. It delves into the psychological, social, and cultural factors that influence consumer behavior, such as perception, learning, motivation, and attitudes. It presents real-life case studies and examples to illustrate how different factors can affect consumer decision-making. The book provides insights into how businesses can better understand and influence consumer behavior to improve their marketing efforts and achieve success.